Physico-Chemical Characteristics of Effluent Exit from Govada Cooperative Sugar Mills At Chodavaram, India - Srinivas, Ch.; Nagamani, Ch.; Gangadhar, M.; Raja Sekhar, M. (Asian Journal of Chemistry, 2010)
Present research work deals with the physical and chemical characteristics of the effluent discharged from the "Govada Cooperative Sugar Mills Ltd.", Chodavaram, Visakhapatnam district, Andhra Pradesh, India. The effluents from different zones of the sugar mill waste are collected. The samples from each zone are taken and the various parameters like colour, odour, temperature, pH, COD, dissolved oxygen, total dissolved solids and total hardness of the effluent are determined. The heavy and toxic metals such as mercury, lead, arsenic, cadmium, etc., which may spoil the aquatic, plants, animals and human bodies are also measured. It is observed from the plots that the pH, dissolved oxygen and heavy metals like mercury, lead and arsenic increases from zone1 to zone 3, also the temperature, COD, total hardness, total dissolved solids and heavy metals of cadmium and chlorine decreases from zone1 to zone 3.